The Effect of Nutrition Supply Duration and KNO3 Concentration on Melon Growth and Yield - Susna, Susna; Mahfudz, Mahfudz; Rauf, Abdul (Universitas Tadulako, 2025)
This study aimed to evaluate the effect of the interaction between the duration of AB-Mix nutrient solution application and the concentration of Potassium Nitrate (KNO3) on the growth and yield of melon plants. The decrease in the sweetness of melon fruit is often associated with the use of low potassium NPK fertilizers. KNO3 is known to play an important role in improving fruit quality, especially sweetness. This study used a split-plot design with four levels of nutrient application duration (D1, D2, D3, D4) as the main plot and three levels of KNO3 concentration (K0=control, K1=850 ppm, K2=1000 ppm) as subplots, replicated four times to produce 48 experimental units. The results showed that the treatment of nutrient solution application interval (D) significantly affected plant height at 2 and 3 WAP and the number of leaves at 2, 3, 4, and 7 WAP, and the number of female flowers. The application of KNO3 (K) fertilizer significantly affected plant height at 2, 3, and 5 WAP, as well as the level of fruit sweetness (Brix). The interaction between the two treatments showed no significant effect on growth parameters and yield. Treatment D4 (the longest watering duration) resulted in a significant increase in plant height, while D3 produced the highest number of leaves and female flowers. A concentration of 1000 ppm KNO3 (K2) alone increased fruit sweetness.